2014
DOI: 10.4103/0970-9290.138293
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum interleukin-8 as a sensitive serological marker in monitoring the therapeutic effect of levamisole in recurrent aphthous ulcers: A randomized control study

Abstract: This study points to the effectiveness of levamisole as an effective adjunct therapy in the routine management of RAU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 1 publication
1
14
0
1
Order By: Relevance
“…Keratinocytes in the pre-ulcerative stage of RAS may produce a significant level of IL-8 which in turn activate neutrophils and attract cytotoxic T cells. Sun et al [44] found that serum concentrations of IL-8 were raised in RAS patients and significantly increased levels of serum IL-8 are found in Behcet's disease patients associated with recurrent oral ulcers [46,47].…”
Section: Role Of Cytokines In Rasmentioning
confidence: 99%
“…Keratinocytes in the pre-ulcerative stage of RAS may produce a significant level of IL-8 which in turn activate neutrophils and attract cytotoxic T cells. Sun et al [44] found that serum concentrations of IL-8 were raised in RAS patients and significantly increased levels of serum IL-8 are found in Behcet's disease patients associated with recurrent oral ulcers [46,47].…”
Section: Role Of Cytokines In Rasmentioning
confidence: 99%
“…Considerable interest has been focused on the potential health benefits of omega-3 fatty acids on many diseases [8,9]. It was also recently discovered that (omega-3 fatty acids) helped defend against ulcers on multiple fronts by augmenting both defensive and offensive factors thus enhancing clearance of inflammation within the lesion promoting tissue regeneration [8,10].…”
mentioning
confidence: 99%
“…Table 1 shows the characteristics of the researched studies based on the examination of interleukin levels. Two articles showed that the research conducted in India [18,21], two articles in Turkey [19,25], three articles in Iran [22][23][24], and one article in China [20]. The number of research subjects in each article consists of 25 to 184 RAS patients, or 551 patients with RAS diagnoses in total.…”
Section: Resultsmentioning
confidence: 99%